Effectiveness of a neonatal COVID-19 response project: A mixed-methods evaluation using the Donabedian model. Issue 1 (February 2023) - Carruthers, Kathryn; Hannis, Dorothy; Robinson, Jonathan; Armstrong, Alan
Abstract: Objective: This article outlines notable findings of a service evaluation of a COVID-19 response project, the Nurture Project (July 2020–March 2021). Method: The Donabedian structure-process-outcome model was used. Mixed-methods online surveys and organisational data were analysed using reflexive thematic analysis and statistical analysis methods. Results: Most staff and service users were satisfied with the project, reporting positive benefits to mental health, child development, and wellbeing. However, project outcome measures (Generalised Anxiety Disorder Scale GAD-7 and the Patient Health Questionnaire PHQ-9) were statistically non-significant. Conclusion: Although the project was considered successful, recommendations for future service evaluation methods, outcome measurement, and future research are provided.